(untitled) (Journal of the College of Basic Education, 2020)
The university stage of the important stages in the life of the individual and imposed by this stage of the demands reflected in the role of mental engineering, which helps the person to change by reforming his thinking and refining himself and programming his ambitions and eliminate the fears and misconceptions that exist and stored in the power of the subconscious through his negative thoughts about himself, University students are likely to be more concerned about the future because their feelings and feelings are unstable and they fear that their goals will not be achieved in the future, which may have an impact on their character traits in the later stages of their academic life. Your current search targeted to identify: 1 - the level of psychological engineering students of the Department of Special Education.2 - level of concern for the future students of the Department of Special Education.3 - the correlation between the psychological engineering and the future concern of students of the Department of Special Education. The current research is determined by the students of the Department of Special Education at the Faculty of Basic Education / Mustansiriya University and for both sexes (male and female) for the academic year 2018/2019. The sample of the study reached (160) students from the four study stages in the department. The researcher examined the scale of psychological engineering, the number of paragraphs (44) paragraph and measure anxiety of the future the number of paragraphs (28) paragraph, and after the extraction of honesty and consistency and after the application of the standards on the sample of the research and data analysis and treatment statistically using the appropriate statistical means emerged the results of the research as follows:1- Students of the special education department have psychological engineering.2. Special education students do not have a future concern.3 - There is an inverse relationship between the psychological engineering and the future concern of students of the Department of SpecialEducation. At the conclusion of the research, the researcher presented a number of recommendations and future proposals.